Ser81 Survivin Induced Protein Kinase A (PKA)-dependent Phosphatidylinositol 3-kinase (PI3K) Activity - Ferry Sandra; Roya Khosravi-Far (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Our previous report showed that phosphorylated-survivin at Ser81 induces survivin back loop to activate protein kinase A (PKA) in the cytoprotection mechanism. Activated PKA could possibly induce the cytoprotection via Phosphatydilinositol 3-kinase (PI3K). Therefore our current study was conducted to investigate the possibility of survivin-PKA-PI3K signaling pathway.METHODS: Viral productions by BOSC23 cells of Survivin, Antisense Survivin (Survivin-AS) and Ser81Ala mutant (Survivin-S81A) in pMSCV-IRES-GFP vector with cytomegalovirus (CMV) promoter were conducted. L929 cells were pretreated with/without PKI 6-22 amide and infected with viral particle of Survivin, Survivin-AS, Survivin-S81A or vector only. Cells were harvested, lysed and immunoprecipitated with anti-PI3K (p85) antibody and immunoblotted to detect PI3K (p85) and phospho-(Tyr) p85 PI3K. To confirm PI3K activation, PI3K Activity Assay was conducted by using phosphoinositide fraction containing PtdIns(4,5)P2 and [32P]ATP.RESULTS: Immunoblot and PI3K activity results showed similar results. Upon infection of virus with survivin, a markedly increased level of tyrosine phosphorylation of p85 PI3K or PI3K activity in L929 cells was seen. Low levels of tyrosine phosphorylation of p85 PI3K or PI3K activity were observed for Survivin-AS and Survivin-S81A-viral-infected L929 cells. With higher concentrations of Survivin-viral-infection, levels of tyrosine phosphorylation of p85 PI3K or PI3K activity in L929 cells were gradually increased. However, when L929 cells were pretreated with PKI 6-22 amide, prior to Survivin-viral-infection, level of tyrosine phosphorylation level of p85 PI3K or PI3K activity was detected much lower.CONCLUSION: Our result suggest that Ser81 Survivin play role in inducing PI3K activation and the Survivin-PI3K signaling pathway was PKA-dependent.KEYWORDS: Ser81, Survivin, PKA, PI3K, L929